Total Physical Response (TPR) Method: Is it effective in improving students' Mufradat Mastery? (Experimental Analysis): Metode Total Physical Response (TPR): Apakah efektif dalam meningkatkan Penguasaan Mufradat Siswa? (Analisis Eksperimen) - Mohamad Rian Liputo; Moh. Aldi Fitrah; M. Tegar Nas'da Putra Yunika (Language Development Center, 2024)
Background: Mastery of mufradat (vocabulary) is a key element in learning Arabic, but many students have difficulty remembering and using new vocabulary. The Total Physical Response (TPR) method has proven effective in language teaching. However, its application in the context of Arabic at the primary school level is still minimally discussed. Purpose: This study aims to evaluate the effectiveness of the TPR method in increasing the mastery of Arabic mufradat in grade V students of SD UNG Laboratory. Methods: This study uses an experimental design with pre-test and post-test approaches. The research population is 60 students in class V, with a sample (Random Sampling) of 40 students. It consists of two groups: an experimental group that applies TPR and a control group that uses conventional methods. Data was collected through pre-test and post-test questions and interviews. Results and Discussion: The results showed a significant increase in mufradat mastery in the experimental group. This is based on the output of the “Test Statistic” carried out, the Asymp value—Sig. (2-tailed) for the experimental class of 0.000. Because the value of 0.000 is less than 0.05, it can be concluded that there is a difference between the results of the pre-test and the post-test of the experimental class. In other words, the Total Physical Response (TPR) method is effective in increasing the mastery of Mufradat for Grade V students of SD UNG Laboratory. Conclusion and Implications: This study concluded that the Total Physical Response (TPR) method effectively increased the mastery of Arabic mufradat by 20 words from the experimental and control classes. The implications of these findings encourage educators to adopt interactive techniques such as TPR in Arabic language teaching and provide recommendations for developing a curriculum that is more responsive to student needs. This research also opens up opportunities for further studies on applying TPR in a broader context with more diverse mufradat.